Anal ultrasonography in monitoring and postoperative evaluation of anorectal malformations - Vivas-Colmenares, Grecia Victoria (2021)
Objectives: We aimed to describe anal ultrasound for monitoring anorectal malformations. Methods: A descriptive and retrospective study of patients diagnosed and/or intervened with anorectal malformations rated by anal ultrasonography, between 2016-2017, was performed. We employed a transducer of 10 megahertz to identify the anatomy of the anal channel. Results: Eight patients, 5 men and 3 women were included, with a mean of 8.37 years old (range, 3-11). Three patients had a diagnosis of an anterior anus (not operated). Surgery was performed in 5 patients: 2 had a rectourethral fistula, 1 had a rectovesical fistula, and 1 had a rectovestibular and a perineal fistula. The most significant ultrasound findings were partial absence of the anterior part of the external sphincter, internal sphincter hypertrophy in the middle channel, and absence of internal sphincter in the median and high channel plus the absence of external sphincter in the anterior region. These results belonged to a patient with clinical incontinence and to 2 patients that were previously diagnosed with an anterior anus. Conclusions: Anal ultrasonography is a non-invasive method, economic, and feasible to be performed without anesthesia. It offers useful anatomical information to establish the best therapeutic option. Its main limitation is the unfeasibility of carrying it out on patients under 3 years old.